2011
DOI: 10.1186/1465-9921-12-40
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between FEV1 change and patient-reported outcomes in randomised trials of inhaled bronchodilators for stable COPD: a systematic review

Abstract: BackgroundInteractions between spirometry and patient-reported outcomes in COPD are not well understood. This systematic review and study-level analysis investigated the relationship between changes in FEV1 and changes in health status with bronchodilator therapy.MethodsSix databases (to October 2009) were searched to identify studies with long-acting bronchodilator therapy reporting FEV1 and health status, dyspnoea or exacerbations. Mean and standard deviations of treatment effects were extracted for each arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 43 publications
(25 reference statements)
10
80
2
4
Order By: Relevance
“…A similar lack of concordance between FEV1 and SGRQ has been observed in numerous other bronchodilator studies [12].…”
Section: Discussionsupporting
confidence: 84%
“…A similar lack of concordance between FEV1 and SGRQ has been observed in numerous other bronchodilator studies [12].…”
Section: Discussionsupporting
confidence: 84%
“…It is well established that there is, at best, a modest correlation between FEV 1 , the primary measure of disease severity in COPD, and clinical outcomes such as respiratory health-related quality of life and dyspnoea,19 20 and FEV 1 does not fully explain the morbidity associated with COPD. In this regard, our findings extend the results of other recent studies that demonstrated a relationship between CT metrics of COPD and clinically relevant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that azithromycin can improve lung function in patients with OB/BOS, but a larger number of patients are needed to see this effect. However, if this is the case, and larger studies are able to determine a statistically significant benefit of azithromycin in OB/BOS, it will be important to also consider whether such a difference is clinically meaningful 33 . As the timing of the initiation of azithromycin in the course of OB naturally varied in these studies, it is also unknown whether earlier therapy might prevent progression.…”
Section: Discussionmentioning
confidence: 99%